Prognostic Markers of Acute Suppurative Lung Disease - D. L. Fetlam; A. G. Chumachenko; M. D. Vyazmina; V. V. Moroz; A. N. Kuzovlev; V. M. Pisarev (Общая реаниматология, 2024)
The mortality rate among patients with acute suppurative lung diseases (ASLD) in the ICU reaches 30%. Early, pathogenetically relevant biomarkers are needed to ensure personiﬁcation and better eﬃcacy of ASLD treatment. Numeric variations in the counts of immune system cells in patient’s blood can be viewed as such candidate biomarkers.The aim of the study. Identiﬁcation of potential markers predicting ASLD outcome after community-acquired pneumonia and COVID-19.Materials and methods. The study included 216 in-hospital patients aged 18-87 with ASLD after community-acquired pneumonia with (N=81) and without (N=135) COVID-19 history.Results. Patients survival after COVID-19 was linked to lymphocyte count on Day 1 of hospital stay (hazard ratio, HR=5.9 95%CI 0.9–37.4; P=0.0188, log-rank test). In patients who had not have COVID-19, a diﬀerence in survival was associated with lymphocyte (HR=2.9 95%CI 1.0–8.4; P=0.0184, log-rank test; N=135), and monocyte counts (HR=2.7 95% CI 0.8–9.5; P=0.0196, log-rank test) on Day 1 of hospital stay. Patients’ survival after COVID-19 infection depended on SII (systemic immune-inﬂammation index. HR=9.3 95%CI 1.7–49.8; P=0.0124, log-rank test; N=81, SIRI (systemic inﬂammatory response index, HR=7.2 95%CI 1.4–36.6; P=0.0339, log-rank test; N=81) and NLR (neutrophil-to-lymphocyte ratio, HR=9.6 95%CI 1.8–52.0; P=0.0108; log-rank test; N=81) values on Day 1 of hospital stay. In patients who did not have COVID-19 SII values had no inﬂuence on survival.Conclusion. The lymphocyte count makes it possible to predict outcomes of pleural empyema, regardless of patient’s history of COVID-19, i. e. a decrease in the lymphocyte count below 1.2×10⁹ in 1 L is associated with fatal outcome. Monocyte count carries prognostic information for cases of pleural empyema without previous COVID-19 infection. As for the relative indicators, SIRI, SII and NLR values measured on Day 1 in the hospital were predictors of ASLD outcome only in patients after COVID-19 infection, i. e., higher values were associated with increased risk of death, with NLR index being the most informative. Overall severity of illness above 10 scores by CIRS was associated with an unfavorable ASLD outcome, regardless of patient’s history of COVID-19.